Analisis Pemberdayaan Masyarakat Sekitar Dark Tourism Destination "Museum Sisa Hartaku" dengan RETS Framework - Reynaldi Dwi Junianta; Yuda Fathi Albani; Bunga Ira Widiastuti; Muhammad Fadhilah Husain (Jurnal Ilmu Manajemen, 2025)
This study aims to analyze the impact of the dark tourism destination "museum sisa hartaku" on the community around the tourist destination using the Rural Empowerment of Tourism Scale (RETS) approach. The measurement with RETS examines aspects of psychological, social, and political empowerment. Dark tourism destinations are a form of niche tourism that seeks to highlight the dark side of an area and turn it into a tourist attraction. The presence of dark tourism destinations in communities affected by disasters is expected to have an empowering effect. The research method uses a mixed method in an effort to obtain data and conduct analysis using SPSS and SEM-AMOS. The results show that the community agrees that they have been empowered psychologically and socially, but doubts whether they have been empowered politically. The implications of the study indicate that RETS can be used to measure community empowerment around dark tourism, and also how residents around the tourist destination "museum sisa hartaku" need to be more politically empowered.